Stakeholder participation in current ecotourism for sustainability of Malaysia - Kwong, Kok Onn; Velan Kunjuraman,; Jayaraj Vijaya Kumaran,; Muhamad Azahar Abas, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This review on ecotourism in Malaysia, Southeast (SE) Asia examines the motivations and satisfaction levels of major stakeholders, aiming to fill a gap in understanding their participation. Royal Belum State Park (RBSP) is known for its rich biodiversity, cultural significance and Indigenous communities, making it an ideal destination for ecotourism. Protected areas such as RBSP, play an important role in providing ecosystem services, preserving biodiversity and offering spaces for local communities. Accordingly, ecotourism at RBSP should balance the biodiversity conservation with needs of the locals. This requires active stakeholder participation, where the interests and rights of all involved parties are recognized and integrated into ecotourism management and decision-making. The study focuses on tourists’, local community and other important stakeholders’ motivations, particularly their desire to experience nature and how this insight can inform more effective management policies and promote sustainability in tourism activities. The review identifies a research gap in SE Asian ecotourism, particularly in the application of social theories and mixed-methods. The study advocates for integrating both qualitative and quantitative methods to improve the reliability of findings and better address the needs of various stakeholders. The ultimate goal is to enhance ecotourism sustainability and stakeholder engagement at RBSP by informing management policies that balance conservation with local development. By improving understanding of tourist preferences, the study seeks to support responsible tourism practices that benefit both the environment and local communities.